Validation and inter-laboratory study of selective hydride generation for fast screening of inorganic arsenic in seafood - Marschner, Karel; Pétursdóttir, Ásta H; Bücker, Patrick; Raab, Andrea; Feldmann, Jörg; Mester, Zoltán; Matoušek, Tomáš; Musil, Stanislav (Analytica chimica acta, 2019)
It is advisable to monitor and regulate inorganic arsenic (iAs) in food and feedstuff. This work describes an update and validation of a method of selective hydride generation (HG) with inductively coupled plasma mass spectrometry (ICP-MS) for high-throughput screening of iAs content in seafood samples after microwave-assisted extraction with diluted nitric acid and hydrogen peroxide. High concentration of HCl (8 M) for HG along with hydrogen peroxide in samples of a same concentration as used for extraction leads to a selective conversion of iAs to volatile arsine that is released and transported to the detector. A minor contribution from methylarsonate (≈20% to iAs) was found, while HG from dimethylarsinate, trimethylarsine oxide is substantially suppressed (less than 1% to iAs). Methodology was applied to Certified Reference Materials (CRMs) TORT-3, DORM-3, DORM-4, DOLT-4, DOLT-5, PRON-1, SQID-1 and ERM-CE278k, in some of them iAs has been determined for the first time, and to various seaweed samples from a local store. The results were always compared with a reference method and selectivity of iAs determination was evaluated. An inter-laboratory reproducibility was tested by comparative analyses of six fish and four seaweed samples in three European laboratories, with good agreement of the results. The method of HG-ICP-MS is sensitive (limit of detection 2 μg kg-1 iAs), well suited for screening of large number of samples and selective at iAs concentration levels at which maximum limits are expected to be set into EU legislation for marine samples.
Keywords: mořské řasy; arsen; Decapodiformes; Perchlorates; vodík; Hydrogen; Squalidae; Selective hydride generation; mlži; Decapoda (Crustacea); Arsenic; Bivalvia; peroxid vodíku; Mass Spectrometry; Certified reference materials; Interlaboratory comparison; Hydrogen Peroxide; měkkýši, korýši; Inorganic arsenic; limita detekce; Hydrochloric Acid; Speciation analysis; kontaminace potravin; Animals; Fish Proteins, Dietary; zvířata; Shellfish; kyselina chlorovodíková; Seaweed; perchloráty; Dogfish; Limit of Detection; Inductively coupled plasma mass spectrometry; potravní rybí proteiny; hmotnostní spektrometrie; Decapoda; Food Contamination